2018
DOI: 10.3390/su10103660
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multivariate Ordered Probit Model to Understand Household Vehicle Ownership Behavior in Xiaoshan District of Hangzhou, China

Abstract: With the rapid increase of motorization in China, transitions have taken place in regards to traditional private transportation modes. This paper aims to understand four types of vehicle ownership within a household, including automobile, motorcycle, electric bicycle and human-powered bicycle. This study presents a cross-sectional multivariate ordered probit model, with a composite marginal likelihood estimation approach that accommodates the effects of explanatory variables, and capturing the dependence among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…A significant ρ indicates interdependence between the error terms. A positive value of ρ is considered “promotive” between the measured pair of equations, while a negative value of ρ is “substitutive” [ 40 ]. The STATA command “mvprobit” was used to estimate the parameters β and ρ .…”
Section: Methodsmentioning
confidence: 99%
“…A significant ρ indicates interdependence between the error terms. A positive value of ρ is considered “promotive” between the measured pair of equations, while a negative value of ρ is “substitutive” [ 40 ]. The STATA command “mvprobit” was used to estimate the parameters β and ρ .…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we use the composite marginal likelihood (CML) estimation method to estimate the multivariate probit model, because the CML method can provide the consistent estimators for both coefficients of explanatory variables and correlations in the error covariance matrix. When the full information maximum likelihood estimation procedure is overly computationally intensive, the composite maximum likelihood method can be an alternative [39,40]. Bhat [41] has demonstrated that the CML method has advantages in computational convenience and stability in spite of some efficiency loss.…”
Section: Modeling Methodologymentioning
confidence: 99%
“…Based on an ordered probit model, the risk degree model of bridge damage caused by the collision of disabled ships was established and applied to analyze the risk degree of bridge damage [39]. Ma and Jie aimed to understand four types of vehicle ownership within a household, including the automobile, motorcycle, electric bicycle, and human-powered bicycle [40]. The study presented a cross-sectional multivariate ordered probit model with a composite marginal likelihood estimation approach, which accommodated the effects of explanatory variables and captured the dependence among the propensity of households for vehicle ownership.…”
Section: Probit Modelmentioning
confidence: 99%